Types of reliability of the KTK gross motor coordination test for children and adolescents: A systematic review - Sanchez-Macedo, Lucila; Vidal-Espinoza, Ruben; Fuentes-Lopez, Jose; Vargas-Ramos, Eliseny; Gomez-Sanchez, Edward; Urra-Albornoz, Camilo; Gomez-Campos, Rossana; Cossio-Bolaños, Marco (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The Körperkoordinationstest für kinder (KTK) is of great use in the field of physical education, rehabilitation and sports science. Its application involves rigorous control in terms of reliability. This review verifies the types of reliability used. The Pubmed database was used, including studies from the period 2016 to 2020. The keywords used were: motor coordination, motor competence, KTK, children, reliability. Ten cross-sectional studies were selected. The age ranges and sample size ranged from 4 to 14 years old and includes a sample size from 64 to 3738. Of the 10 studies, 2 used three reliability criteria (stability, equivalence, and internal consistency), 3 used measures of stability, and 4 used measures of equivalence. The reported stability measures ranged from 0.60 to 0.99, equivalence measures from 0.75 to 0.99, and internal consistency measures from 0.95. In conclusion, it was verified that the cross-sectional studies evaluating the KTK tests were generally conducted on children of both genders and applied in age ranges from 4 to 14 years old as suggested by the original proposal and the types of reliability used varied among the studies from moderate to excellent.